Organosilylated complex [Eu(TTA)3(Bpy-Si)]: A bifunctional moiety for the engeneering of luminescent silica-based nanoparticles for bioimaging - Duarte, Adriana P. [UNESP]; Mauline, Léïla; Gressier, Marie; Dexpert-Ghys, Jeannette; Roques, Christine; Caiut, José Maurício A.; Deffune, Elenice [UNESP]; Maia, Danielle C. G. [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Ferreira, Antonio A. P. [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Menu, Marie-Joëlle (American Chemical Society (ACS), 2013)
A new highly luminescent europium complex with the formula [Eu(TTA) 3(Bpy-Si)], where TTA stands for the thenoyltrifluoroacetone, (C 4H3S)COCH2COCF3, chelating ligand and Bpy-Si, Bpy-CH2NH(CH2)3Si(OEt)3, is an organosilyldipyridine ligand displaying a triethoxysilyl group as a grafting function has been synthesized and fully characterized. This bifunctional complex has been grafted onto the surface of dense silica nanoparticles (NPs) and on mesoporous silica microparticles as well. The covalent bonding of [Eu(TTA)3(Bpy-Si)] inside uniform Stöber silica nanoparticles was also achieved. The general methodology proposed could be applied to any silica matrix, allowed high grafting ratios that overcome chelate release and the tendency to agglomerate. Luminescent silica-based nanoparticles SiO2-[Eu(TTA)3(Bpy-Si)], with a diameter of 28 ± 2 nm, were successfully tested as a luminescent labels for the imaging of Pseudomonas aeruginosa biofilms. They were also functionalized by a specific monoclonal antibody and subsequently employed for the selective imaging of Escherichia coli bacteria. © 2013 American Chemical Society.
Keywords: Chelating ligands; Escherichia coli bacteria; General methodologies; Mesoporous Silica; Pseudomonas aeruginosa; Selective imaging; Silica nanoparticles; Thenoyltrifluoroacetone; Chelation; Grafting (chemical); Ligands; Luminescence; Monoclonal antibodies; Nanoparticles; Silica; Silicon